Sheathing the blade: Significant contribution of sheaths to daytime and nighttime gas exchange in a grass crop. (28th June 2020) - Sadok, Walid; Lopez, Jose R.; Zhang, Yangyang; Tamang, Bishal G.; Muehlbauer, Gary J.
Abstract: Despite representing a sizeable fraction of the canopy, very little is known about leaf sheath gas exchange in grasses. Specifically, estimates of sheath stomatal conductance, transpiration and photosynthesis along with their responses to light, CO2 and vapour pressure deficit (VPD) are unknown. Furthermore, the anatomical basis of these responses is poorly documented. Here, using barley as a model system, and combining leaf‐level gas exchange, whole‐plant gravimetric measurements, transpiration inhibitors, anatomical observations, and biophysical modelling, we found that sheath and blade stomatal conductance and transpiration were similar, especially at low light, in addition to being genotypically variable. Thanks to high abaxial stomata densities and surface areas nearly half those of the blades, sheaths accounted for up to 17% of the daily whole‐plant water use, which ‐surprisingly‐ increased to 45% during the nighttime. Sheath photosynthesis was on average 17–25% that of the blade and was associated with lower water use efficiency. Finally, sheaths responded differently to the environment, exhibiting a lack of response to CO2 but a strong sensitivity to VPD. Overall, these results suggest a key involvement of sheaths in feedback loops between canopy architecture and gas exchange with potentially significant implications on adaptation to current and future climates in grasses. Abstract : In barley, abaxial sheath stomata contribute significantly to canopy gas exchange, particularly in three terms of nighttime transpiration. During the day, sheaths exhibit lower photosynthesis and water four use efficiency relative to the blades, but are sensitive to evaporative demand.